The eyeball collector - Higgins, F. E. (Square Fish, 2011)
Hector Fitzbaudly travels to Pagus Parvus and Withypitts Hall on his quest for vengeance against the man responsible for his poverty, but his adversary, the Eyeball Collector, is a master of disguises who steals jewels from the wealthy to make false eyeballs.